Description of Culicoides (Mataemyia) felippebauerae sp. n., Forcipomyia musae immatures, and occurrence of F. genualis, breeding in banana stems in Brazilian Amazonia (Diptera: Ceratopogonidae) - Spinelli, Gustavo Ricardo (2007)
The following three species of Ceratopogonidae were collected breeding in the rhizomatous herb Phenakospermum guyannense Endl., 1833 in the vicinity of Manaus, Brazil, a new species, Culicoides (Mataemyia) felippebauerae Spinelli, Forcipomyia (Forcipomyia) genualis (Loew), and F. (Phytohelea) musae Clastrier & Dellécole. C. (M.) felippebauerae is described and illustrated as adult, pupa, and fourth instar larva, the adult compared with the adult of C. barthi Taveres and Souza and larva and pupa with those of C. dicrourus Wirth & Blanton and C. macieli Tavares & Ruiz, the only species with known immatures in the subgenus. The pupa and fourth instar larva of F. (P.) musae are described and illustrated and compared with immatures of F. (P.) edwardsi Saunders.